ANALISIS SEDIMENTASI PANTAI SURABAYA-SIDOARJO PASCA PEMBANGUNAN JEMBATAN SURAMADU DAN PERISTIWA LAPINDO MENGGUNAKAN CITRA SATELIT SPOT-4 - Mayasari , Ratna; Sukojo, Bangun Muljo; Setiyoko, Andie (Departemen Teknik Geomatika ITS, 2011)
Sedimentation is the process of formation or deposition of sediment. Coastal areas north of East Java, especially Surabaya and Sidoarjo, is an entity that has a different pattern of development of coastal shoreline. This study used data satellite SPOT-4 and Landsat-7 ETM, where medium-resolution satellite has a swath width to the SPOT-4 60km and 185km for the Landsat-7 ETM. Sedimentation can be well described by using the red band of each satellite image was first converted into reflectance values to eliminate the atmospheric effects. The algorithm used is algorithm Budhiman to get the value of TSS (Total Suspended Solid). From the data processing and analysis we found that sedimentation along the coast of Surabaya-Sidoarjo dominated by TSS values 25-125 mg/L. In addition sedimentation can also be seen from the addition of 147.978 ha of land area between the years 2003 and 2006 and 213.888 ha between 2006 and 2009. From these results can be indicated that the sedimentation rate is increasing after the suramadu bridge construction and Lapindo events.